Pd-catalyzed enantioselective intramolecular α-arylation of α-substituted cyclic ketones: facile synthesis of functionalized chiral spirobicycles1. Issue 17 (7th May 2015) - Fan, Lulu; Takizawa, Shinobu; Takeuchi, Yoshiki; Takenaka, Kazuhiro; Sasai, Hiroaki
<x xml:space="preserve">Abstract</x> Synthesis of chiral spirocyclic ketones was accomplished via the Pd-catalyzed intramolecular α-arylation of α-substituted cyclic ketones. The obtained spirocyclic ketone could be converted into an acid–base organocatalyst.